HAJJ SERVICE OPTIMIZATION: THE STRATEGIC ROLE OF IMMIGRATION IN SUPPORTING SMOOTH EMBARKATION AND DEBARKATION IN BALIKPAPAN - Iskandar, Tatang; Nur Laeli, Sefia (Institut Agama Islam Negeri Metro, 2024)
This study examines the improvement of Hajj services and the role of immigration officers in the embarkation and debarkation process of pilgrims at Sultan Aji Muhammad Sulaiman Sepinggan International Airport Balikpapan. With the increasing number of Hajj pilgrims every year, this research highlights the importance of effective Hajj management and the establishment of a team of Hajj Organizing Officers (PPIH) to ensure the smooth process of departure and return of pilgrims. This research's primary focus is optimising airport services, the immigration process, accommodation, catering, and security of the pilgrims. The results show that the Directorate General of Immigration plays a crucial role in expediting immigration checks, while inter-agency cooperation is needed to ensure successful Hajj management. The study concludes that improved services and inter-agency coordination can enhance the Hajj experience.